THE SCIENTIFIC-CUM-SUFISTIC INTERPRETATION OF SAID NURSI IN KULLIYYAT RASAIL AL-NUR (TAJDID: Jurnal Ilmu Ushuluddin, 2024)
The Qur'an is a holy book that contains many valuable lessons, requiring interpretation (tafsir) to understand its contents in depth. Ahmad Mustafa al-Maraghi, through his work Tafsir al-Mara>ghi>, presents one of the most remarkable interpretations with a social approach that is relevant to the needs of modern society. Meanwhile, Said Nursi, a contemporary scholar, offers a unique paradigm of scientific interpretation (tafsir 'ilmi) that emphasizes the essence of faith and monotheism, oriented toward the ultimate purpose of the hereafter. This study employs a library research method to explore and identify the novelty of scientific interpretation in the work Kulliyya>t Rasa>il al-Nu>r. The approach used in this research is tafsir s'ilmi. The findings reveal two main conclusions. First, Said Nursi's scientific interpretation emphasizes the essence of faith and monotheism with an eschatological orientation, differing from other scientific interpreters. Second, the novelty of tafsir 'ilmi proposed by Said Nursi is divided into three aspects: (1) in terms of its characteristics, it adopts a scientific-cum-sufistic style; (2) in its perspective and interpretation of nature, it applies two meanings, namely harfi and ismi; and (3) in terms of its impact and the interrelation between science and the Asma’ al-Husna, it fosters the integration of general sciences (science) and religious knowledge.